Magnetic Foreign Body Ingestion in Children: The Attractive Hazards - Anna Lin; Lawrence Chi Ngong Chan; Kam Lun Ellis Hon; Siu Yan Bess Tsui; Kristine Kit Yi Pang; Hon Ming Cheung; Alexander K. C. Leung (Case Reports in Pediatrics)
Foreign body ingestions are frequent in the childhood population. Most foreign bodies are passed spontaneously through the gastrointestinal tract. However, on occasion, they can also be a rare cause of morbidity and even mortality, such as in the case of multiple magnetic foreign body ingestion, which can cause injury via magnetic attraction through bowel walls. We present two cases of multiple magnetic foreign body ingestion, which to our knowledge are the first ones reported in Hong Kong. One patient presented with shock and intestinal necrosis requiring extensive intestinal resection, whereas the other patient had no gastrointestinal injury but surgical removal was deemed necessary.